2019
DOI: 10.3892/mmr.2019.10767
|View full text |Cite
|
Sign up to set email alerts
|

A simple, efficient and economical method for isolating and culturing human umbilical cord blood‑derived mesenchymal stromal cells

Abstract: Mesenchymal stromal cells (MScs) hold broad therapeutic potential in various diseases, however, it is difficult to produce sufficient numbers of MSCs for clinical application, therefore, improved culture systems are required. The present study aimed to develop a novel method for isolating and culturing human umbilical cord blood-derived mesenchymal stromal cells (hucB-MScs). a sequential culture method was developed that uses two types of culture media to optimize the isolation and culture of hucB-MScs. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) can be obtained from umbilical cord, amniotic membrane, adipose tissue, and so on (Cho et al 2019;Han et al 2014;Hendrijantini and Hartono 2019;Zhang et al 2019). MSCs are usually used for the treatment of traumatic and degenerative diseases due to its extensive source, self-renewal potential, multi-lineage differentiation, and immunoregulatory ability (Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) can be obtained from umbilical cord, amniotic membrane, adipose tissue, and so on (Cho et al 2019;Han et al 2014;Hendrijantini and Hartono 2019;Zhang et al 2019). MSCs are usually used for the treatment of traumatic and degenerative diseases due to its extensive source, self-renewal potential, multi-lineage differentiation, and immunoregulatory ability (Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the era of stem cell research, mesenchymal stem cells have been one of the key sources of cell-based therapies [51]. Different research groups identified, isolated, and compared the cellular morphology, surface markers, and differentiation abilities of MSCs derived from different sources [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A lot of work has been performed to date to investigate the possible therapeutic effects of MSCs in different acute kidney injury models [16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are undifferentiated, self-renewable, non-hematopoietic adult stem cells of mesodermal origin [1]. These multipotent stem cells are broadly distributed in the body and can be relatively easily isolated from various tissues, such as bone marrow, umbilical cord blood, fat, muscle, periosteum, lung, testis, and dermis [2][3][4][5][6][7][8][9][10][11][12][13][14]. MSCs can differentiate into both mesenchymal and non-mesenchymal lineages, including differentiation toward adipocytes, chondrocytes, osteocytes, skeletal muscle cells, renal cells, and smooth muscle cells [9][10][11]15].…”
Section: Introductionmentioning
confidence: 99%